(untitled) (Research, Society and Development, 2018)
The Ribeirão Candidópolis Hydrographic Basin, located in the municipality of Itabira (MG), is the main source of raw water supply for the Pureza System, which supplies treated water to a significant portion of the urban population of this city. Despite the importance of Ribeirão Candidópolis to the municipality, in recent years it has been suffering from inadequate soil management in its basin. This work aimed to elaborate the diagnosis of the environmental and fluvial conditions of a Ribeirão Candidópolis stretch from the observation and evaluation of indicators of degradation and establish proposals for its restoration. It was verified that the degradation state of Ribeirão Candidópolis in the analyzed section can be classified as "medium" in relation to its physical aspects, while the environmental quality received the worst evaluation, resulting mainly from the scarcity or absence of ciliary forest. Among the restoration techniques to be used, we highlight the recovery of riparian vegetation by means of the implementation of buffer zones and the use of anti-erosion biodegradableblanket or tires for soil reinforcement, together with the vegetal recomposition, to control the observed erosive processes. In this scenario is essential to prepare studies and propose measures for the restoration of the river to maintain the quality and quantity of water, especially for public supply purposes.